LEADERSHIP AS AN “ENTRY POINT” FOR COMBATING CORRUPTION AND SHAPE ON ANTI FRAUD CULTURAL SYSTEMS (Case study in Singapore) - Abdul Rasyid Sahar; Roy Valiant Salomo (Asia Pacific Fraud Journal, 2018)
Singapore is a country with the lowest corruption rate in Asia. In the last two decades, the amount of data and facts released by international agencies such as Transparency International and The Political and Economic Risk Consultancy show this its entirety. This paper tries to describe the determinant aspect in eradicating corruption; how the strategy of eradicating corruption; and also recognizes the steps and strategies of corruption eradication experience in Singapore that can be “lesson-learned” by other countries especially Indonesia. Based on existing precedents and postulates, it can be concluded that an entry point for eradicating corruption in Singapore stems from strong political support (strong leadership) of party elites, government and society, as well as increased official incentives and public institutional reconstruction efforts.